Cellular distribution of 92-kd type IV collagenase/gelatinase B in human hepatocellular carcinoma. - Ashida, K. (1996)
To examine the possible involvement of gelatinase B in human hepatocellular carcinoma (HCC), cellular localization of transcripts and protein of gelatinase B were studied by using in situ hybridization and immunohistochemistry. Transcripts for gelatinase B were observed in tumor cells in 22 cases of 27 HCCs and also in dysplastic nodules. However, there was no significant difference in the expression among histological grades of HCC. The expression was mostly homogeneous, but the intensity varied with the nodules. Of 13 cases with capsular invasion, 12 expressed gelatinase B, whereas 10 of 14 without capsular invasion did (P < 0.05). Gelatinase B transcripts were commonly observed in the sinusoidal cells of the hepatic lobules, in mesenchymal cells both in fibrous capsules and around the necrosis, and also in some undefined cells of the portal tracts of noncancerous liver. Localization of gelatinase B protein was mostly similar to but sometimes different from that of the transcripts in cancer nodules. In conclusion, the expression of gelatinase B appears to be an important characteristic of malignant transformation of hepatocytes. The findings suggest that gelatinase B synthesized by cancer cells plays an important role in the growth and invasion of HCC by degrading surrounding extracellular matrices.